2018
DOI: 10.1101/250068
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The effect of education on adult mortality, health, and income: triangulating across genetic and policy reforms

Abstract: 1AbstractOn average, educated people are healthier, wealthier and have higher life expectancy than those with less education. Numerous studies have attempted to determine whether these differences are caused by education, or are merely correlated with it and are ultimately caused by another factor. Previous studies have used a range of natural experiments to provide causal evidence. Here we exploit two natural experiments, perturbation of germline genetic variation associated with education which occurs at con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 45 publications
0
21
0
1
Order By: Relevance
“…Compulsory schooling laws were introduced in many European countries and the United States during the 20 th Century (Brunello, Fort, & Weber, 2009). An extensive literature in economics and public health has used these reforms to examine the causal effect of schooling duration on a range of adult specific diseases and risk factors (Banks & Mazzona, 2012;Davies, Dickson, Davey Smith, van den Berg, & Windmeijer, 2018;Dursun & Cesur, 2016;Glymour, Kawachi, Jencks, & Berkman, 2008;Huang, 2015;Nafilyan, Avendano, & De Coulon, 2017;Nguyen et al, 2016;Schneeweis, Skirbekk, & Winter-Ebmer, 2014), health behaviors (Jurges, Reinhold, & Salm, 2011;Silles, 2015), health-related knowledge (Johnston, Lordan, Shields, & Suziedelyte, 2015), and mortality (Albouy & Lequien, 2009;Clark & Royer, 2013;Gathmann, Jurges, & Reinhold, 2015;Lager & Torssander, 2012;Lleras-Muney, 2005). However, a recent review and metaanalysis of the health effects of compulsory schooling laws identified a paucity of research on biomarkers of health (Hamad, Elser, Tran, Rehkopf, & Goodman, 2018).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Compulsory schooling laws were introduced in many European countries and the United States during the 20 th Century (Brunello, Fort, & Weber, 2009). An extensive literature in economics and public health has used these reforms to examine the causal effect of schooling duration on a range of adult specific diseases and risk factors (Banks & Mazzona, 2012;Davies, Dickson, Davey Smith, van den Berg, & Windmeijer, 2018;Dursun & Cesur, 2016;Glymour, Kawachi, Jencks, & Berkman, 2008;Huang, 2015;Nafilyan, Avendano, & De Coulon, 2017;Nguyen et al, 2016;Schneeweis, Skirbekk, & Winter-Ebmer, 2014), health behaviors (Jurges, Reinhold, & Salm, 2011;Silles, 2015), health-related knowledge (Johnston, Lordan, Shields, & Suziedelyte, 2015), and mortality (Albouy & Lequien, 2009;Clark & Royer, 2013;Gathmann, Jurges, & Reinhold, 2015;Lager & Torssander, 2012;Lleras-Muney, 2005). However, a recent review and metaanalysis of the health effects of compulsory schooling laws identified a paucity of research on biomarkers of health (Hamad, Elser, Tran, Rehkopf, & Goodman, 2018).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Individual level data are valuable because it can be used to perform some sensitivity analyses that cannot be done with summary data, e.g. the use of interactions ( 87 , 90 , 91 ), and triangulating MR estimates with alternative causal inference strategies ( 16 , 18 , 103 ). Other advantages of using individual level data from the same sample are that causal estimates are robust to misspecification of the SNP-exposure association model, and when LD patterns are needed an external reference panel can be avoided.…”
Section: Introductionmentioning
confidence: 99%
“…Future studies using Mendelian Randomization (MR) on genetic data may test this hypothesis, which would be supported by a unidirectional causal path from IQ-related genetic variants to sleep timing. We are aware of one such study 23 , which found minimal causal influence of education on chronotype using an education polygenic score which is also associated with intelligence 24 .…”
Section: Discussionmentioning
confidence: 99%